Exploration of mental health outcomes of community-based intervention programs for adult male survivors of childhood sexual abuse - Yun, Sung Hyun; Fiorini, Lydia (Groupwork, 2020)
This study aims to evaluate the effectiveness of clinical treatment for male survivors of childhood sexual abuse (CSA) who deal with depression, anxiety, stress, and posttraumatic stress disorder (PTSD). Secondary data was used in the study, and a one-group pretest-posttest design was employed to compare pretest (n = 346) with posttest (n = 91) scores. The analysis shows statistically significant improvements with respect to depression, anxiety, stress, and PTSD after treatment. There was no statistically significant difference between individual and mixed treatment (including group and individual counselling) regarding alleviating mental health symptoms. Despite a lack of statistical difference between treatments, the results confirm that interventions were equally effective in reducing negative mental health symptoms. The study contributes to the generation of evidence-based knowledge for treatment and its ability to reduce negative mental health symptoms for adult male survivors of CSA. It also informs practitioners of the utility of a male-specific treatment modality based on trauma-focused cognitive and behavioral therapies (TF-CBT) and the gender role strain paradigm (GRSP). Key Words: Adult Male Survivors, Childhood Sexual Abuse, Mental Health, Evaluation